TUBERCULOUS LYMPHADENITIS IN AFGHAN REFUGEES - Ullah, Shafi; Shah, Syed Humayun; Rehman, Aziz Ur; Kamal, Arshad; Begum, Norin (Journal of Ayub Medical College Abbottabad, 2002)
Background: Tuberculosis is a disease of poor countries. The war-stricken Afghan refugees, owing to abject poverty, illiteracy, lack of social awareness and poor hygienic conditions, are highly susceptible to tuberculosis. This study was conducted to assess the frequency of peripheral lymph node tuberculosis in Afghan refugees. Methods: One thousand lymph node biopsies from Afghan refugees were examined histopathologically. The diagnosis was undertaken on morphological grounds. Lymph nodes containing caseating epithelioid cell granulomas were identified as tuberculous. Age and sex of the patient and site of biopsy were also recorded. Results: Sixty nine percent of the nodes revealed tuberculosis. Male: Female ratio was 1:1.2. Of all the cases 72% cases were 10-30 years of age. The most common site involved was neck that was involved in 79% of cases. Conclusions: Tuberculous lymphadenitis has an alarmingly high prevalence in Afghan refugees of NWFP.